Thulium-doped fiber as gain medium and saturable absorber for pulsed fiber laser - Ahmad, Muhammad Taufiq (2015)
The study focuses on developing and demonstrating fiber laser applications using newly developed thulium-doped fiber (TDF). TDF functions as two different devices in this study. Firstly, TDF is use as gain medium to increase gain significantly at 2 μm wavelength. It specifically functions at that region due to pumped thulium ions reaction force an emission at 2 μm region. The energy transition of 3F4→3H6 can be obtained by pumping TDF with 802 nm and 1552 nm source. Secondly, TDF is use as passive saturable absorber. Passive saturable absorber works to generate self-starting pulse. This happen when TDF absorb lights that going through it until accumulated energy reached saturation level. At saturation level, accumulated energy will discharge and forcing pulse to occur. Instead of TDF, carbon nanotubes (CNT) are also used as saturable absorber in generating pulse. Pulse, or commonly known as ultra-fast pulse are divided into two; Q-switched pulse and mode-locked pulse. Q-switched pulse is a short, high energy pulse from a laser modulating through the intracavity losses and the quality (Q) factor of the ring laser. The microsecond pulse usually occurs in kHz frequency. High pulse energy will force the frequency of the pulse to increase, while the pulses become thinner. Mode-locked pulse is an ultra-short pulses from laser cavity with duration of nanosecond to femtosecond. Due to some circumstances, mode-locked pulse can only appears in a very low power laser cavity. As a result, no stimulated emission will occur since loss is higher than the power. In most cases, mode-locked pulse has a fixed frequency and pulse width depending on the cavity, even the power is changed.